Turmeric (curcumin) remedies gastroprotective action - Kumar Yadav, Santosh; Sah, Ajit Kumar; Kumar Jha, Rajesh; Sah, Phoolgen; Shah, Dev Kumar (Pharmacognosy Reviews, 2013)
The purpose of this review is to summarize the pertinent literature published in the present era regarding the antiulcerogenic property of curcumin against the pathological changes in response to ulcer effectors (Helicobacter pylori infection, chronic ingestion of non‑steroidal anti‑inflammatory drugs, and exogenous substances). The gastrointestinal problems caused by different etiologies was observed to be associated with the alterations of various physiologic parameters such as reactive oxygen species, nitric oxide synthase, lipid peroxidation, and secretion of excessive gastric acid. Gastrointestinal ulcer results probably due to imbalance between the aggressive and the defensive factors. In 80% of the cases, gastric ulcer is caused primarily due to the use of non‑steroidal anti‑inflammatory category of drug, 10% by H. pylori, and about 8‑10% by the intake of very spicy and fast food. Although a number of antiulcer drugs and cytoprotectants are available, all these drugs have side effects and limitations. In the recent years a widespread search has been launched to identify new antiulcer drugs from synthetic and natural resources. An Indian dietary derivative (curcumin), a yellow pigment found in the rhizome of Curcuma longa, has been widely used for the treatment of several diseases. Epidemiologically, it was suggested that curcumin might reduce the risk of inflammatory disorders, such as cancer and ulcer. These biological effects are attributed to its anti‑inflammatory and antioxidant activities. It can, therefore, be reported from the literature that curcumin prevents gastrointestinal‑induced ulcer and can be recommended as a novel drug for ulcer treatment.
Keywords: Curcumin; gastroprotective; Helicobacter pylori; non‑steroidal anti‑inflammatory drugs; oxidative stress